2017
DOI: 10.1002/jcb.26007
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate Mofetil and Rapamycin Induce Apoptosis in the Human Monocytic U937 Cell Line Through Two Different Pathways

Abstract: Transplant vasculopathy may be considered as an accelerated form of atherosclerosis resulting in chronic rejection of vascularized allografts. After organ transplantation, a diffuse intimal thickening is observed, leading to the development of an atherosclerosis plaque due to a significant monocyte infiltration. This results from a chronic inflammatory process induced by the immune response. In this study, we investigated the impact of two immunosuppressive drugs used in therapy initiated after organ transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Subsequently, function enrichment analyses were performed on these immune mRNAs of IDO1-related differential miRNAs, finding that enrichment results mainly in the regulation of inflammatory response, lipid and atherosclerosis, TNF signaling pathway, MAPK signaling pathway, IL-17 signaling pathway, and so on. Previous research has discovered the relationship between organ transplantation and atherosclerosis, where organ transplantation leads the development 61 . TNF has been confirmed as a key factor that regulates cell inflammation response and mediates tumor rejection 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, function enrichment analyses were performed on these immune mRNAs of IDO1-related differential miRNAs, finding that enrichment results mainly in the regulation of inflammatory response, lipid and atherosclerosis, TNF signaling pathway, MAPK signaling pathway, IL-17 signaling pathway, and so on. Previous research has discovered the relationship between organ transplantation and atherosclerosis, where organ transplantation leads the development 61 . TNF has been confirmed as a key factor that regulates cell inflammation response and mediates tumor rejection 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Vitiallo et al proved that mammalian targets of rapamycin inhibitors (siromimus and everolimus) showed a very potent anti-inflammatory effect by decreasing the response of neutrophils and decreasing both release of VEGF and IL-8 [23]. Moreover, Nowak et al demonstrated the pro-apoptotic effect of sirolimus induced by oxidized LDL as well as mycophenolate mofetil-both drugs significantly increased the cell death in a monocyte cell lineage [24]. To our knowledge, there are no trials assessing the impact of IS drugs on the functional properties of hematopoietic stem cells; most of the studies are focused on the transplantation of these cells in the treatment of hematological diseases.…”
Section: Discussionmentioning
confidence: 99%
“…For experimental purposes, cells were treated with tacrolimus (0.1 μM and 1 μM), MMF (1 or 10 μg/ml) or a combination of tacrolimus and MMF (0.1 μM and 1 μg/ml, 0.1 μM and 10 μg/ml, 1 μM and 1 μg/ml, and 1 μM and 10 μg/ml, respectively) as described elsewhere (7,8). Control cells were treated with vehicle alone.…”
Section: Methodsmentioning
confidence: 99%